Public policy initiatives to promote the employment of persons with disabilities: from ensuring access to positions within the civil service to implementing support mechanisms for their integration into cooperatives and social economy entities - Arnáez Arce, Vega María (Cooperativismo & Desarrollo, 2025)
The UN 2030 Agenda establishes a global normative framework aimed at human well-being, environmental sustainability, economic prosperity, peace, and universal access to justice. As a new social pact, it requires international and local cooperation between public and social actors to achieve inclusive and equitable development. This implies reviewing and integrating the Sustainable Development Goals (SDGs) into national regulations through mechanisms that promote intergovernmental coordination. A central aspect is the full inclusion of persons with disabilities in personal, social, and working life, ensuring their effective participation. This analysis examines current legislation on access to employment for this group in two main areas: first, the legal provisions governing their incorporation into public employment, with particular focus on the Basque Public Employment Law; second, public procurement as a strategic tool to foster their access to the labor market, guaranteeing their priority consideration in contract award procedures.